Peran Fear Of Missing Out (FOMO) Memediasi Pengaruh Promo Twin Date Event dan Scarcity Message terhadap Impulse Buying (Studi Pada Generasi Z Pengguna Aplikasi Shopee di Kabupaten Purworejo) - Putri, Riska Anisa; Puspitasari, Intan; Runanto, Dedi (Syntax Corporation, 2025)
This study aims to analyze the role of Fear of Missing Out (FOMO) in mediating the effects of Twin Date Event promotion and Scarcity Message on impulse buying among Generation Z users of the Shopee app in Purworejo Regency. This research adopts a quantitative approach with a survey method, and data were collected through an online questionnaire. The results indicate that both the Twin Date Event promotion and Scarcity Message have a positive and significant effect on impulse buying, with FOMO serving as a mediator that strengthens the relationship between these two factors and impulse buying. These findings suggest that the feeling of FOMO triggered by Twin Date Event promotions and Scarcity Messages can encourage impulsive buying behavior among Generation Z. This study provides valuable insights for businesses in designing more effective marketing strategies by utilizing psychological elements such as FOMO to boost sales.